An Integrated Information Retrieval Framework for Managing the Digital Web Ecosystem - Zhu, Dengya; Nimmagadda, Shastri; Reiners, Torsten (2018)
The information explosion constrains the Digital Web Ecosystem exploration and makes challenging in retrieving relevant information and knowledge using Web search tools. The existing tools are not well integrated, and search results are inadequately managed. In this article, we describe effective information retrieval services for users and agents in various digital Web ecosystem scenarios. A novel Integrated Information Retrieval Framework (IIRF) is proposed, which employs the Web search technologies and traditional database searching techniques to provide comprehensive, dynamic, personalized, and organization-oriented information retrieval services, ranging from the Internet, intranet, to personal desktop. Experiments are carried out demonstrating the improvements in the search process with an average precision of Web search results to standard 11 recall level, attaining improvement from 41.7% of a comparable system to 65.2% of search. A 23.5% precision improvement is achieved with the framework. The comparison made among search engines presents similar development with satisfactory search results.